2021
DOI: 10.20944/preprints202108.0283.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recent Expeditious Growth of Type 1 Diabetes in the Gulf Arab Countries

Abstract: The incidence of Type 1 Diabetes (T1D) in the Arab world, particularly, oil and gas rich Gulf Cooperative Council (GCC) countries has more than doubled in the last twenty years. Therefore, there is a dire need for careful systematic familial cohort studies, especially in high-risk populations. Several immunogenetic factors affect the pathogenesis of the disease. Genes in the human leukocyte antigen (HLA) account for the major genetic susceptibility to the disease. The triggering agents initiate disease onset b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Recent epidemiological data showed a fast-growing incidence rate in the Middle East and Asia 54,55 . It is suggested that in addition to genetic and environmental risk factors, consanguinity is one of the potential risk factors for type 1 diabetes mellitus in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological data showed a fast-growing incidence rate in the Middle East and Asia 54,55 . It is suggested that in addition to genetic and environmental risk factors, consanguinity is one of the potential risk factors for type 1 diabetes mellitus in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the susceptibility loci identified in the recent years have a clear role in modulation of T cell development and activation, indicating that common biological pathways may be implicated in the etiology of different autoimmune diseases (7). A number of recently published reviews and reports provided comprehensive information about the genetic risk factors (MHC and non-MHC loci), epidemiological aspects and immune system involvement in T1DM patients from Kuwait (8)(9)(10)(11). These reports include information on genetic factors which influence both susceptibility and resistance to T1DM (8).…”
Section: Introductionmentioning
confidence: 99%